Bioengineered collagen graft for urethral reconstruction in animal models / Ganes Vythilingam - Ganes, Vythilingam (2018)
With the increase incidence of hypospadias and urethral stricture, the need for a surgically efficient and cost effective graft to reconstruct the urethra has become paramount, especially in view of the complications arising from presently used technologies. Current available surgical techniques require harvesting of grafts from autologous sites resulting in complications. In addition, lack of tissue availability and added patient discomfort further limits present surgical options. Cell based approaches have shown progress in this area. However, these have been associated with high costs and regulatory hurdles. An acellular graft using relatively inexpensive materials that has been previously approved by regulatory bodies and possesses good regenerative potential is thus more likely to be used in clinical practice. In this thesis we examined and reengineered four tubular collagen grafts of different densities over a period of 3 years using initially rat tail collagen and subsequently bovine collagen, which has been previously approved by FDA. This effort has resulted in the development of a relatively easy to fabricate acellular bovine collagen graft with the desired mechanical property that allows better surgical and regenerative performance of damaged urethra. Grafts were analytical and empirical mechanical tested prior to the in-vivo study. 2 cm of the urethra was resected in each of the 65 (N=65) male New Zealand rabbits and replaced with the grafts. Rabbits were evaluated at 1, 3, 6, 9 and 11 months using visual examination and contrast voiding cystourethrography. Biopsies of repaired sites from euthanized rabbits were then subjected to histological examination and immunohistochemistry. The outcome of the four different types of engineered acellular collagen grafts were compared. This multi-centric study revealed from the contrast voiding cysto-urethrography that the initial produced acellular collagen tube had a 40% failure rate as compared to the final version, with a 10% failure iv rate. The variation in density between the engineered four grafts appeared to influence the functional outcome. It was noted on histology that urothelial cells favored higher density grafts compared to smooth muscle cells. Smooth muscle cells preferred grafts with less density. The adequate smooth muscle cells remodeling of the engineered graft influenced by density modification of its matrix is a finding that has not been described yet. Improved smooth muscle regeneration is an advantage, as the primary pathology in urethral stricture is due to muscular fibrosis. Furthermore, spontaneous urothelial coverage of the grafts and smooth muscle cell migration in the implanted graft could be demonstrated by standard histology and immunohistochemistry. The final graft subjected to X-Ray sterilization according to ISO-11137 standards, (N=4 rabbits), showed similar graft function as compared to non-sterilized grafts. Preliminary results of a pilot dog study with 3 animals implanted with a 4cm tubular graft also demonstrated the functional potential of the engineered grafts in a clinically relevant length of urethral defect. The final acellular graft developed may have the potential to be an off the shelf product; is easy for the surgeon to work with, regenerative efficient and safe for urethroplasty